Exploring Students' Engagement in Blended Learning: Insights from ELT Classroom at an Islamic University - Paramma, Muhammad Azwar; Tajrin, Indrawati Amrullah; Nurhuda, Pradicta (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This study explores students’ engagement in a blended learning environment within an English Language Teaching (ELT) course at the English Language Education Study Program, Sultan Aji Muhammad Idris State Islamic University of Samarinda, Indonesia. Utilizing a descriptive survey design, the research combined quantitative data from Learning Management System (LMS) analytics with qualitative data from open-ended questionnaire responses to provide a comprehensive understanding of students' engagement patterns and perceptions. The findings revealed that while students generally demonstrated high levels of engagement, particularly in collaborative and discussion-based tasks, several challenges were also identified, including technical barriers, difficulties with digital literacy, and a desire for more synchronous interaction. Students expressed positive perceptions of the flexibility and accessibility offered by blended learning, although they also recommended improvements in LMS navigation and task instructions. Cultural factors, such as communal learning values, appeared to influence students' engagement behaviours. The study highlights the importance of designing interactive, supportive, and culturally responsive blended learning environments to optimize student engagement and learning outcomes in higher education.